ANALISIS HOME INDUSTRI PEMBUATAN KERUPUK OPAK DI DESA JAYA BAKTI KECAMATAN MADANG SUKU I KABUPATEN OKU TIMUR - Agoes Thony (Jurnal Bakti Agribisnis, 2019)
The objectives of this study were to: 1) determine the technique of making opak crackers in Jaya Bakti Village, Madang Suku I District, East OKU Regency, 2) determine the income and break-even point of the home industry for making opak crackers in Jaya Bakti Village, Madang Suku I District, East OKU Regency , 3) knowing the added value of the home industry for making opak crackers in Jaya Bakti Village, Madang Suku I District, East OKU Regency, 4) knowing whether the home industry for making opak crackers in Jaya Bakti Village, Madang Suku I District, East OKU Regency is profitable and feasible to develop. The results showed that: 1) the technique of making opaque crackers is quite easy, namely by grated cassava, seasoned (garlic, coriander and salt), then molded and steamed for ± 2 minutes for one steaming opaque cracker, then dried in the sun for ± 2 days, after the raw dry opaque crackers are packaged and then marketed. So, the process of making opak crackers takes ± 5 days, 2) the revenue obtained from the home industry for making opak crackers is IDR 735,000 / PP, with a production cost of IDR 501,362 / PP, with a fixed cost of IDR. 69,444, - / PP and a variable cost of 428,000, - / PP, then the income is Rp. 233,638 .- / PP or Rp. 1,401,828 .- / month, 3) the added value in making opak crackers is Rp. 333,638, - / PP obtained from revenue less intermediate costs. The intermediate cost is obtained from the total production cost, namely Rp. 501,362, - / PP minus family labor costs of Rp. 100,000, - / PP so that the total intermediate cost is Rp. 401,362, - / PP, 4) the level of profit based on the acceptance of the value is more than 1, namely the R / C Ratio of 1.47 which means that the opaque cracker home industry is profitable. Meanwhile, based on the level of profit from income the value is more than the prevailing bank interest rate, namely B / C Ratio of 0.47, which means that the home industry for making opaque crackers is non feasible. The production BEP value is Rp. 53.27, - / kg / PP, the BEP value of Rp. 559,361, - / PP, and the BEP value is Rp. Rp. 4.386, - / kg / PP, so this business can be said to be functionally feasible. In addition, the total assets invested in the home industry during the year or the ROI value resulted in a profit of 0.38%, meaning that for the home industry, opaque cracker making for one year generated a profit of 0.38%.